Frequency of Systemic Diseases and Medication Intake by Patients Referred to the Department of Oral Medicine of Hamadan Dental School - Sharifi, Shiva; Roshanaei, Qodratollah; Samie, Lida; Ahmadi-Motamayel, Fatemeh (Journal of Dental School, 2020)
Objectives Due to advances in knowledge and treatment of diseases, life expectancy has increased worldwide. This study aimed to determine the prevalence of systemic diseases and medication intake by dental patients referred to dental clinic of Hamadan Dental School. Methods A total of 800 patients referred to the Department of Oral Medicine from October 2013 to May 2014 were studied. The data extracted from patient charts included demographic data, systemic diseases, and medication intake, which were analyzed using the Chi-square test and Fisher’s exact test with SPSS version 16.0. Results Of all, 28.8% of participants were males and 71.2% were females. The mean age of participants was 32.3 years. The total prevalence of systemic diseases was 30.5%. The most common condition was endocrine diseases. The total prevalence of medication intake was 20% and the most common medications taken were supplements and antihypertensive medications. Conclusion The results of the present study showed that systemic diseases were prevalent in dental patients. Dentists and dental students must take a precise medical and medication history from patients before starting any dental procedure to prevent medical emergencies